2020
DOI: 10.1111/jpi.12707
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves the effect of cryopreservation on human oocytes by suppressing oxidative stress and maintaining the permeability of the oolemma

Abstract: Cryopreservation causes cryoinjury to oocytes and impairs their developmental competence. Melatonin (MLT) can improve the effect of cryopreservation in animal oocytes. However, no such studies on human oocytes have been reported. In this study, collected in vitro‐matured human oocytes were randomly divided into the following groups: fresh group, MLT‐treated cryopreservation (MC) group, and no‐MLT‐treated cryopreservation (NC) group. After vitrification and warming, viable oocytes from these three groups were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…The cryopreservation of mouse [ 27 ], bovine [ 50 ], pig [ 51 ], and human oocytes [ 52 ] increases oxidative stress, although exogenous melatonin reduce oxidative stress in vitrified-warmed oocytes [ 30 , 53 ]. The Nrf2 signaling pathway is an important intracellular antioxidant signaling pathway, critical for maintaining redox balance [ 31 , 54 ]. Melatonin is a regulatory molecule of the Nrf2 protein [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cryopreservation of mouse [ 27 ], bovine [ 50 ], pig [ 51 ], and human oocytes [ 52 ] increases oxidative stress, although exogenous melatonin reduce oxidative stress in vitrified-warmed oocytes [ 30 , 53 ]. The Nrf2 signaling pathway is an important intracellular antioxidant signaling pathway, critical for maintaining redox balance [ 31 , 54 ]. Melatonin is a regulatory molecule of the Nrf2 protein [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation can destroy some proteins in oocytes, e.g., porcine Nrf2, human aquaporin 1 (APQ1) [ 31 ], goat CDK1 [ 65 ], and mouse Mad2 [ 66 ], etc. After the vitrification of porcine COC oocytes, proteomics analysis revealed that 59 proteins were down-regulated [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[51][52][53] Furthermore, studies, where melatonin was administered to improve the quality of the embryo and increase the implantation rate in in vitro fertilization and embryo transfer (IVF-ET) pregnancies, have been conducted in humans for many years; however, there have been no reports of side effects to date. [54][55][56][57] There have also been no reports of melatonin causing side effects in either adults or neonates. Many animal studies conducted on pregnant subjects and researches performed in human neonates suggest that the melatonin administration might be safe in human pregnancy as well.…”
Section: Mel Atonin Safe T Y During Preg Nan C Ymentioning
confidence: 99%
“…24 In human studies, oral administration of melatonin improved oocyte quality, and increased the number of mature eggs, the rate of high-quality embryos and clinical pregnancy rate. 17,[25][26][27][28] Melatonin supplementation in the culture medium (mIVF) reversed vascular dysfunction and arterial hypertension in adult IVF mice. 29 Therefore, we hypothesized that mIVF might reverse impaired glucose metabolism in IVF mice offspring.…”
Section: Introductionmentioning
confidence: 99%